Legume–rhizobium dance: an agricultural tool that could be improved? - Basile, Laura Ana (2021)
The specific interaction between rhizobia and legume roots leads to the development of a highly regulated process called nodulation, by which the atmospheric nitrogen is converted into an assimilable plant nutrient. This capacity is the basis for the use of bacterial inoculants for field crop cultivation. Legume plants have acquired tools that allow the entry of compatible bacteria. Likewise, plants can impose sanctions against the maintenance of nodules occupied by rhizobia with low nitrogen-fixing capacity. At the same time, bacteria must overcome different obstacles posed first by the environment and then by the legume. The present review describes the mechanisms involved in the regulation of the entire legume–rhizobium symbiotic process and the strategies and tools of bacteria for reaching the nitrogen-fixing state inside the nodule. Also, we revised different approaches to improve the nodulation process for a better crop yield.